Adjustment of dryland stream channels over four decades of urbanization. (December 2017) - Chin, Anne; Gidley, Rachel; Tyner, Lauren; Gregory, Ken
Abstract: Human settlements are increasingly expanding into drylands and mountain areas that are less accommodating to urban communities, creating hazards related to the conveyance of water and sediment. Comparatively few studies of urbanization effects on streams have focused on drylands, especially steep terrains. Development of the town of Fountain Hills in the foothills of the McDowell Mountains (Arizona, USA) since the 1970s provides an example of dryland streams adjusting to urbanization over several decades. Urbanization has introduced numerous roads with dip crossings that fragment channels, causing management challenges. Field surveys in 1987, 2006, and 2016 showed that wash channels in urban areas are up to ten times larger than comparable natural channels. Roads have exerted a spatial pattern of geomorphic influence, where channels downstream of dip crossings are narrower and deeper than those upstream, reflecting erosion with input of urban drainage. Repeat measurements showed that the pattern of downstream incision and upstream accretion has become less evident in the recent decade. The muted response by 2016 results from evolving management that has improved the conveyance of water and sediment, including stormwater controls and erosion protection. Additionally, comparison of channel changes at dip crossings with those at culverted crossings revealed greater impact at dip crossings. Less morphological change at culverts suggests more effective throughput of water and sediment. Results demonstrate successful adaptive management including decisions to employ culverts in recent developments. The evolving landscape of Fountain Hills provides a possible template for understanding and predicting changes in other dryland areas undergoing urbanization.